Nutritional supplement use in a UK high-performance swimming club - Newbury, J. W.; Sparks, S. A.; Cole, M.; Kelly, A. L.; Gough, L. A. (Nutrients, 2023)
The aim of this study was to observe the nutritional supplement practices of highly trained swimmers on a national talent pathway, since it is often reported that swimmers engage in widespread supplement use at the elite level. Thus, this study employed a validated supplement intake questionnaire with forty-four swimmers from a high-performance swimming club, which had three distinct talent stages: development (aged 11-14 years, n = 20), age-group (aged 13-17 years, n = 13), and national level (aged = 16 years, n = 11). Ninety-eight percent of the interviewed swimmers reported using at least one supplement, with performance (34%) and recovery (19%) cited as the primary reasons. National swimmers used more total supplements (8.1 ± 3.4 supplements) compared to age-group (4.8 ± 2.0 supplements, p = 0.003, g = 1.17) and development (3.9 ± 1.7 supplements, p < 0.001, g = 1.69) swimmers, mostly because of a greater intake of ergogenic aids (2.4 ± 1.4 supplements vs. age-group: 0.5 ± 0.5 supplements, p < 0.001, g = 1.12; vs. development: 0.1 ± 0.2 supplements, p < 0.001, g = 1.81). Parents/guardians were the primary supplement informants of development swimmers (74%, p < 0.001, V = 0.50), whereas performance nutritionists informed ~50% of supplements used by age-group and national swimmers (p < 0.001, V = 0.51). Based on these results, supplement education and greater focus on basic sport nutrition practices may be required for parents/guardians at the development level. Moreover, further research is needed to support the high number of ergogenic aids used by national swimmers, with the efficacy of these supplements currently equivocal in the applied setting.